The Influence of Work Discipline and Work Motivation on Employee Performance at CV Wisata PO Rukun Jaya - Sapitri, Ajeng; Fa’uzobihi, Fa’uzobihi; Imanudin, Kafffah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Based on the results of studies conducted by researchers, it appears that the performance of employees at the PO Rukun Jaya company is very poor. This condition is characterized by employees often arriving late and decreasing company income every year. This is due to the lack of work discipline and work motivation of PO employees. Rukun Jaya, with high discipline and providing the right motivation, employees or subordinates will comply with all existing regulations so that work implementation can proceed according to predetermined plans, and employee performance will increase. This research aims to determine the influence of work discipline and work motivation partially or simultaneously on the performance of PO employees. Rukun Jaya. The population in this study were PO employees. Rukun Jaya. The sampling technique in this research is a saturated sample, namely taking the entire population to be used as a sample. The sample taken in this research was 30 respondents. The method for collecting this data uses a questionnaire, while the method in this research uses multiple linear regression analysis. The results of this research show that work discipline has a positive and significant effect on performance seen from tcount>ttable, namely 3,413 > 1.701, motivation has a positive and significant effect on performance also seen from tcount>ttable, namely 33,046> 1.701 and simultaneously the variables of discipline and motivation have a positive effect and significant for performance is shown by Fcount > Ftable, namely 28,137 > 3.34. Of all the results, both partially and simultaneously, the sig value is smaller than 0.05 or 0.000 < 0.05, meaning that Ha is accepted and Ho is rejected, which means that the variables of work discipline and motivation together have a positive and significant influence on employee performance. P.O. Rukun Jaya.